PENGARUH PENEMPATAN KERJA, PENGEMBANGAN KARIR, DAN KAPABILITAS INDIVIDU TERHADAP KINERJA KARYAWAN PADA PT. JAPFA COMFEED INDONESIA TBK UNIT MAROS - SP, Muh. Aldi; Hanafi, Muh. Alam Nasyrah; Nurjaya, Muhammad (Jurnal Kajian Ekonomi dan Manajemen Indonesia (JKEMI), 2023)
The purpose of this study was to determine the effect of job placement, career development and individual capabilities on employee performance at PT Japfa Comfeed Indonesia Tbk Maros Unit. The variables used are job placement, career development, individual capabilities, and performance. Data collection methods through questionnaires distributed to employees of PT Japfa Comfeed Indonesia Tbk Maros Unit. The type of research used is quantitative research. samples taken were 55 respondents with sampling techniques using simple random sampling or simple random samples. Sample calculation technique with the Slovin formula. The data analysis method used in this study uses multiple linear regression analysis, correlation coefficient test, determination coefficient test, partial test (T-test), and simultaneous test (F test). all analysis methods are processed using the SPSS Version 26.0 software program. The results showed that partially the job placement variable had no effect and was significant to the employee performance variable, partially the career development variable had an effect and was significant to the employee performance variable, the individual capability variable had an effect and was significant to the employee performance variable. The results showed simultaneously that the variables of job placement, career development, and individual capabilities had a significant effect on team member performance variables